Forensic age estimation via 3-T magnetic resonance imaging of ossification of the proximal tibial and distal femoral epiphyses: Use of a T2-weighted fast spin-echo technique. (March 2016) - Ekizoglu, Oguzhan; Hocaoglu, Elif; Inci, Ercan; Can, Ismail Ozgur; Aksoy, Sema; Kazimoglu, Cemal
Highlights: Magnetic resonance imaging (MRI) analysis of the knee is a suitable radiation-free tool for age estimation. Future studies via different MRI sequences will contribute to the field. Stage 3 of both epiphysis at the knee joint indicates 14 years of age for males. Stage 5 of distal femoral epiphysis indicates 21 years of age for both sexes. Abstract: Radiation exposure during forensic age estimation is associated with ethical implications. It is important to prevent repetitive radiation exposure when conducting advanced ultrasonography (USG) and magnetic resonance imaging (MRI). The purpose of this study was to investigate the utility of 3.0-T MRI in determining the degree of ossification of the distal femoral and proximal tibial epiphyses in a group of Turkish population. We retrospectively evaluated coronal T2-weighted and turbo spin-echo sequences taken upon MRI of 503 patients (305 males, 198 females; age 10–30 years) using a five-stage method. Intra- and interobserver variations were very low. (Intraobserver reliability was κ  = 0.919 for the distal femoral epiphysis and κ  = 0.961 for the proximal tibial epiphysis, and interobserver reliability was κ  = 0.836 for the distal femoral epiphysis and κ  = 0.885 for the proximal tibial epiphysis.) Spearman's rank correlation analysis indicated a significant positive relationship between age and the extent of ossification of the distal femoral and proximal tibial epiphyses ( p  < 0.001). Comparison of male and female data revealed significant between-gender differences in the ages at first attainment of stages 2, 3, and 4 ossifications of the distal femoral epiphysis and stage 1 and 4 ossifications of the proximal tibial epiphysis ( p  < 0.05). The earliest ages at which ossification of stages 3, 4, and 5 was evident in the distal femoral epiphysis were 14, 17, and 22 years in males and 13, 16, and 21 years in females, respectively. Proximal tibial epiphysis of stages 3, 4, and 5 ossification was first noted at ages 14, 17, and 18 years in males and 13, 15, and 16 years in females, respectively. MRI of the distal femoral and proximal tibial epiphyses is an alternative, noninvasive, and reliable technique to estimate age.